Materi-Materi Pilihan dalam Parenting Education menurut Munif Chatib - purnama, sigit (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2016)
This article aims to describe Munif Chatib thinking about materials in parenting education. This type of research is literature that emphasizes the significance of processed philosophically and theoretically used to examine the primary and secondary data sources. The process of data collection is done by reading the symbolic and semantic level, recording the data card, and coding. The data were analyzed descriptively through data reduction, data classification, data display. The analytical method used is Verstehen (understanding). The results showed that: (1) Chatib thoughts about parenting education materials based on the perspective of children and parents. He saw that the child is born it brings nature of goodness, and the development is influenced by genes and environment. Being a parent it is a precious grace of God and a golden opportunity for a good charity. Therefore, do not be afraid to get married and have children. Such views inspired and by integrating various fields of science, namely religion (al-Qur'an-Hadith and sirrah), developmental psychology, child psychology, and recent findings about the brain, nerves, and intelligence. (2) parenting education materials include: changing the paradigm of a child, the child's ability to explore, discover the talent of children, choosing the right school, and became a teacher for children.